PEMIBINAAN DAN PELATIHAN OLIMPIADE SAINS NASIONAL (OSN) TINGKAT KOTA BIDANG MATEMATIKA BAGI SISWA SMA NEGERI 7 DENPASAR - I Made Surat; I Komang Sukendra; I Dewa Putu Juwana; I Wayan Widana (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Maximum achievement will be shown by the birth of qualified and highly competitive science competition champions who are ready to compete at the national level. This activity aims to provide guidance and training to improve students' abilities in Mathematics in order to prepare students for Olympiad activities. This activity is expected to increase students' understanding and competitive spirit in solving math olympiad questions. In achieving this goal, coaching and training activities on material and Olympic questions were held in order to prepare students to face city-level competitions in mathematics. This Community Service activity in the form of coaching and training, began with a discussion with the head of SMA Negeri 7 Denpasar which was then followed by the submission of an Olympic supervisor from the school to the chairman of the LPPPM Universitas PGRI Mahadewa Indonesia. Coaching activities are carried out for eight meetings which are held every Friday at 12.00-13.30 WITA. This activity is carried out from the beginning of August to the second week of October. Step by step in intensive guidance activities can be done smoothly according to plan. The results of guidance, observation and evaluation during the process of this activity showed that there was interest and a good response from the participants towards the material presented